SPEAKING DIFFICULTIES IN ENGLISH DEBATING PRACTICES FOR DEBATING COMPETITION: STUDENTS’ PERSPECTIVE - Rambe, Leini Nadira; Yuliarti, Yuliarti; Helnaz, Regina Nopia (JR-ELT (Journal of Research in English Language Teaching), 2025)
This study explores the speaking difficulties encountered by English as a Foreign Language (EFL) learners preparing for the national round of National University Debating Championship (NUDC) 2025, after passing on the regional ropund. Employing a qualitative approach, the research analyzed data from observation notes and semi-structured interviews with four debaters from Institut Seni Budaya Indonesia Aceh. The analysis focused on four key themes: fluency and coherence, lexical resource, grammatical accuracy, and pronunciation. Findings indicate that these speaking difficulties function as significant barriers that dictate debating performance. Fluency and coherence emerged as foundational requirements; without them, students experienced cognitive overload and total withdrawal. Lexical gaps triggered fragmented performances where logical depth was undermined by low processing speed. While grammatical accuracy was treated pragmatically, it remained essential for maintaining an intelligibility ceiling. Furthermore, pronunciation acted as a critical persuasion driver, allowing speakers to project authority and mask other linguistic weaknesses. The study concludes that the transition from a survivalist speaker to a strategic debater is only possible when learners move past low thresholds in these four categories. These results suggest that pedagogical interventions should focus on linguistic automaticity and cognitive load management to equip EFL learners for high-pressure competitive debating environments.